Assessing Very Early Infant Diagnosis Turnaround Times: Findings from a Birth Testing Pilot in Lesotho. (19th December 2017) - Gill, Michelle M.; Hoffman, Heather J.; Mokone, Majoalane; Tukei, Vincent J.; Nchephe, Matsepeli; Phalatse, Mamakhetha; Tiam, Appolinaire; Guay, Laura; Mofenson, Lynne
Abstract : Very early infant diagnosis (VEID) (testing within two weeks of life), combined with rapid treatment initiation, could reduce early infant mortality. Our study evaluated turnaround time (TAT) to receipt of infants' HIV test results and ART initiation if HIV-infected, with and without birth testing availability. Data from facility records and national databases were collected for 12 facilities offering VEID, as part of an observational prospective cohort study, and 10 noncohort facilities. HIV-exposed infants born in January–June 2016 and any cohort infant diagnosed as HIV-infected at birth or six weeks were included. The median TAT from blood draw to caregiver result receipt was 76.5 days at birth and 63 and 70 days at six weeks at cohort and noncohort facilities, respectively. HIV-exposed infants tested at birth were approximately one month younger when their caregivers received results versus those tested at six weeks. Infants diagnosed at birth initiated ART about two months earlier (median 6.4 weeks old) than those identified at six weeks (median 14.8 weeks). However, the long TAT for testing at both birth and six weeks illustrates the prolonged process for specimen transport and result return that could compromise the effectiveness of adding VEID to existing overburdened EID systems.